Design And Implementation of Garbage Bin Management with Location and Sms Alerts Using Gsm And GPS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Garbage bins remain uncollected for long periods of time putting the lives of marketeers at risk in an event that there is Cholera outbreak especially during the rainy season. This happens because the Kitwe City Council does not have a system that monitors the garbage levels and notifies the Central Office. To avoid such a situation, this project proposes the design and implementation of a GPS and GSM Based Garbage and Waste Collection Bin Overflow Management System using GPS and GSM technology in providing real time information on the status of the garbage bins, i.e., when they are full so that appropriate action can be carried out. The system notifies the person (Truck Driver) in charge of garbage collection by sending a short message (SMS) and telling them where the full bin is exactly located. Again, after some time the system notifies the Central Office that the message has been sent to the Driver. This development will ultimately save a lot of time especially when the council does not have to go and check the level of garbage in the bin. Besides, it will timely prevent the overflow of garbage since garbage will be collected on time. That is, the council will collect garbage only when it is time to do so rather than routine where even half-full bins are collected.